Studi Literatur: Peran Perpustakaan sebagai Perpustakaan Digital - Oktavia, Diva; Marlini, Marlini; Desriyeni, Desriyeni (TSAQOFAH, 2026)
This study is a literature review that aims to analyze in depth the strategic role of digital libraries in improving the quality of information services in the modern technological era. Digital libraries are positioned as a form of institutional transformation from conventional systems toward a technology-based ecosystem that is dynamic, efficient, and responsive to user needs. Through the use of Information and Communication Technology (ICT), libraries function not only as repositories of electronic collections but also as knowledge centers that support academic activities, research, and lifelong learning. The research employed a qualitative descriptive literature review method by analyzing national and international journal articles, reference books, and government policies related to information digitalization. The findings show that digital libraries contribute to operational efficiency, equitable access to information, the strengthening of digital and information literacy, and enhanced interinstitutional collaboration. However, the success of their implementation is strongly influenced by the quality of infrastructure, the competencies of librarians, and the sustainability of digital management policies. Accordingly, digital libraries play a pivotal role in building an inclusive, knowledgeable, and competitive knowledge-based society in the global era.